The Growth of Electronic-cigarette Use Globally and Its Implications for Australia – A Literature Review - Joul Kassis (Archives of Medicine and Health Sciences)
The usage of electronic cigarettes (e-cigarettes), also known as vaporizers, has grown fast around the world, and people of all ages are joining in on this trend despite the recognized hazards and detrimental side effects on users. Despite the current legal hurdles, Australian smokers have increased their usage of e-cigarettes during the last 10 years. The implications of its use began to raise red lights and became more prevalent in areas where light should be spotted. Recently, and in response to growing concern around young people vaping, the Australian government has changed how e-cigarettes are regulated and more changes might be on the way. In this study, I will explore the development of e-cigarettes and its rise internationally, as well as the risks and benefits of using e-cigarettes that it is believed to have come out with, and ultimately, what its consequences are for the Australian population utilizing studies and surveys from Google Scholar and PubMed.